Substitute of Light Requirement for Germination in Positive Photoblastic Seeds of Inula racemosa - A Critically Endangered Medicinal and Aromatic Plant of North-Western Himalaya, India - Sharma, Rajender Kumar; Bhatia, Bela; Chhibbar, Anju K; Mukherjee, Sayna; Ritika; Kumari, Khushi; Indu (International Journal of Ecology and Environmental Sciences, 2024)
Inula racemosa, commonly known as pushkarmool, has high economic value due to its medicinal and aromatic properties. The species has been over-exploited for commercial purposes and become threatened (critically endangered) in NW Himalaya. The seeds exhibited photo-sensitivity and were complete positive photoblastic. They germinated (80%) only when exposed to light; no germination was recorded in dark. The hydrated seeds required only a brief exposure of light to initiate germination, thus can be categorized under Low-Fluence Responces (LFRs). Under natural field conditions the seeds do not germinated when sown below 1.5 cm soil depth, as the light became limiting factor. Interestingly, GA3 (1 mM) substituted the requirement of light for germination; 70% germination was recorded under complete darkness due to GA3. These observations are completely new for seeds of I. racemosa and discussed in detail. The findings have practical applications for seed-based multiplication of the species.